Evaluation of a multi‐sensor for measuring solution electrical conductivity in coir. Issue 3 (6th April 2021) - Miyamoto, Teruhito; Iwata, Yukiyoshi; Inaba, Satoshi; Kameyama, Koji; Dyck, Miles
Abstract: The simultaneous measurements of both volumetric water content (θ) and electrical conductivity of pore solutions (ECw ) are essential for nutrient solution management within soilless culture systems. The present study was carried out in order to evaluate a capacitance sensor (METER 5TE) for the measurement θ and EC w within coir. Following the evaluation of the spatial sensitivity of the 5TE sensor, a calibration experiment was executed with six levels of θ (0.30, 0.35, 0.40, 0.45, 0.50, and 0.55 m 3 m −3 ) and four levels of KCl solutions (1.0, 3.0, 5.0, and 7.0 dS m −1 ). The measured relationship between θ and dielectric permittivity (εa ) for coir significantly deviated from Topp's equation for organic soil, but was similar to the calibration equation for growing media from the sensor manufacturer and for peat soils. The Hilhorst (2000) model recommended by the manufacturer overestimated ECw within coir. On the other hand, accounting for EC dependency on the real part of the complex dielectric permittivity of the solution within the Hilhorst model will greatly improve ECw prediction. In contrast, the Rhoades (1976) model was more capable of describing the dependence of the apparent soil electrical conductivity (ECa ) on θ and ECw for the coir samples for ECa < 2.9 dS m −1 . Hence, when ECw −ECa −θ relations are known, the capacitance sensor is a powerful tool for horticultural practices because a single measurement can yield both θ and ECw . Core ideas: A capacitance sensor was used to measure θ and ECw within a coir‐based growing media. Dielectric permittivity measured by the sensor was significantly influenced by EC. The Rhoades model performed well for estimating ECw within a coir‐based growing media. Evaluating the EC dependence on εp in the Hilhorst model may improve EC prediction.